Interlab: Interactive Technologies Laboratory - Tori, Romero; Nakamura, Ricardo; Nunes, Fátima; Bernardes Jr., João Luiz; Ferreira, Maria Alice; Ranzini, Edith (Journal on Interactive Systems, 2011)
<!-- p, li { white-space: pre-wrap; } --> <!--StartFragment-->In this paper we present an overview of Interlab, including its origin, research lines and some of the ongoing projects.